A novel rare-earth complex containing hindered phenol and thioether groups for styrene-butadiene rubber/silica composites with improved antioxidative properties. (August 2019) - Zou, Yongkun; He, Jingwei; Tang, Zhenghai; Zhu, Lixin; Liu, Fang
Abstract: A novel rare-earth complex containing hindered phenol and thioether groups (Sm-GMMP) was prepared by using 2-tert-butyl-6-(3-tert-butyl-2-hydroxy-5-methylphenyl) methyl-4-methylp-henyl acrylate (GM), 3-mercaptopropionic acid (MPA) and samarium chloride hexahydrate (SmCl3 ·6H2 O) via Michael addition reaction of sulfydryl with acrylate and coordination reaction. The chemical structure of Sm-GMMP was confirmed by 1 H-NMR, FT-IR, XPS and elemental analysis. It was revealed by the results of the accelerated thermal aging tests, FTIR-ATR, TGA, whiteness and yellowness index that Sm-GMMP significantly improved the thermo-oxidative aging resistance and thermal-oxidative stability of styrene-butadiene rubber/silica composites without discoloration. The outstanding antioxidative ability of Sm-GMMP for SBR/silica composites was attributed to not only the synergistic antioxidative effect between hindered phenol and thioether groups, but also the deactivation role of samarium ions to oxygen free radicals and its excellent thermal stability. Highlights: A novel rare-earth complex containing hindered phenol and thioether groups (Sm-GMMP) was successfully synthesized via Michael addition reaction of sulfydryl with acrylate and coordination reaction. The chemical structure of Sm-GMMP was characterized and confirmed by 1 H-NMR, FT-IR, XPS and elemental analysis. Sm-GMMP revealed superior thermal stability and volatility resistance, and significantly improved the thermal stability and thermo-oxidative aging resistance of styrene-butadiene rubber/silica composites without discoloration.